Practicality of Using Interactive Multimedia Teaching Materials with a STEM Approach in Elementary Schools - Yulyani Yulyani; Yalvema Miaz; Yanti Fitria; Abna Hidayati (Jurnal Penelitian Pendidikan IPA, 2023)
The aim of this research is to describe the practicality of interactive multimedia teaching materials in integrated thematic learning using a STEM approach in elementary schools. This type of research is development research using the 4D model (Define, Design, Develop, and Disseminate). Data collection techniques in practicality tests use practicality questionnaires by educators and students. The data in this practicality instrument uses a practicality formula which is analyzed quantitatively. Based on the results of the practicality test, the interactive multimedia teaching materials with the STEM approach that were developed are included in the very practical category with the percentage of practicality test obtained by teachers with an average score of 97%, very practical and the practicality test obtained by students with an average score of 89%, very practical category. It can be concluded that interactive multimedia teaching materials based on the STEM approach meet the criteria for being very practical